Mediterranean Models of Welfare Towards Families and Women - Pierluigi Grasselli; Cristina Montesi; Paola Iannone (European Regional Science Association (ERSA), 2006)
After an historical Excursus on Malta's history, society, culture and institutions with their effects on female condition and on family structure and concept, the paper gives a survey of most recent Malta's economic and demographic trends with special attention to families and women, based on statistical data of the National Institute of Statistics and on the results of a sample research. After drawing this scenario, the paper makes a short History of Malta's Welfare State specially concerning family and women. In this treatment a deeper investigation is devoted to the latest "Action Plan", the national social plan in its general lines of intervention towards family and women. The strategic lines (public, private, non profit) of welfare mix are examined in relation to their amounts, results and to the coherence with the moving social context. Finally the paper develops a comparison between different european models of welfare towards family, more specifically between Malta and Italy.
Keywords: 330